A Modern Paradise: Garifuna Land, Labor, and Displacement-in-Place. (November 2014) - Mollett, Sharlene
On the Honduran North Coast, the Afro-indigenous Garifuna struggle to maintain access to and control of their ancestral lands. Their concerns are due in part to the Honduran state's long-standing goal of modernizing the North Coast and providing an attractive site for foreign investment in land and tourism. The state's commitment to improving the country's development profile by opening coastal land ownership to foreigners often overlooks international and constitutional recognition of communal forms of land tenure. Ethnographic participant observation in the Garifuna community of Tornabé, a fishing and farming village in the Tela Bay region, supplemented by semistructured interviews, historical data collection, discourse analysis, and research on agrarian and environmental policy, suggests that Garifuna displacement is a product of the state's development imaginaries, which racialize the Garifuna as backward and consider their blackness redeemable only by their labor. En la costa norte de Honduras, los garífunas afro-indígenas luchan por mantener el acceso a y control de sus tierras ancestrales. Sus preocupaciones se deben en parte a la meta de largo plazo del estado hondureño por modernizar la costa norte y hacerla atractiva a la inversión extranjera en tierras y turismo. El compromiso del estado por mejorar el perfil de desarrollo del país accediendo a que exista propiedad extranjera en la región costeña a menudo ignora el reconocimiento constitucional e internacional de formas comunales de tenencia de la tierra. Observación etnográfica participante en la comunidad garífuna de Tornabé, una aldea de pescadores y agricultores en la región de Bahía de Tela, complementada con entrevistas semi-estructuradas, recopilación de datos históricos, análisis del discurso e investigación sobre política agraria y ambiental, sugiere que el desplazamiento forzado garífuna es un producto de imaginarios de desarrollo estatales que los racializan como retrógradas y consideran que su negrura sólo es redimible a través de su trabajo.